2013
DOI: 10.1152/ajpregu.00523.2012
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of high-fat diet on neurovascular function and focal ischemic brain injury

Abstract: -Obesity is a risk factor for stroke, but the early effects of high-fat diet (HFD) on neurovascular function and ischemic stroke outcomes remain unclear. The goal of this study was to test the hypotheses that HFD beginning early in life 1) impairs neurovascular coupling, 2) causes cerebrovascular dysfunction, and 3) worsens short-term outcomes after cerebral ischemia. Functional hyperemia and parenchymal arteriole (PA) reactivity were measured in rats after 8 wk of HFD. The effect of HFD on basilar artery func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 43 publications
(58 reference statements)
6
83
0
1
Order By: Relevance
“…This result suggests that juvenile exposure to HFD for 8 weeks does not cause any significant differences in neuronal death compared to LFD 4 days after ischemia/reperfusion. This result was supported by previous studies that also showed no difference in hippocampal neuronal death between control diet-and HFD-fed groups after 8 weeks in a rat model of global ischemia [19,20]. In addition, our colleagues do not detect any significant differences in neuronal damage between control diet-and HFD-fed groups after 4 weeks in the gerbil model of transient forebrain ischemia [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result suggests that juvenile exposure to HFD for 8 weeks does not cause any significant differences in neuronal death compared to LFD 4 days after ischemia/reperfusion. This result was supported by previous studies that also showed no difference in hippocampal neuronal death between control diet-and HFD-fed groups after 8 weeks in a rat model of global ischemia [19,20]. In addition, our colleagues do not detect any significant differences in neuronal damage between control diet-and HFD-fed groups after 4 weeks in the gerbil model of transient forebrain ischemia [21].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, obesity beginning in childhood decreases cerebral vascular function and exacerbates the damage caused by focal ischemia [3,6,7,17,18]. However, obesity does not cause any significant effects on neuronal cell death or survival after global cerebral ischemia [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in redox biology and aging research (9,21,27,33,37,49,51,52,55,59,65,72,97), the role of ROS in the cerebromicrovascular effects of CR remains elusive. To assess cellular peroxide production, we used the cell-permeant oxidative fluorescent indicator dye CM-H 2DCFDA [5 (and 6)-chloromethyl-2=,7=-dichlorodihydrofluorescein diacetateacetyl ester; Invitrogen, Carlsbad, CA] as we previously reported (16,86).…”
Section: Animals and Dietmentioning
confidence: 99%
“…For example, increased cerebral infarct size and poor outcomes of stroke have been observed in a number of genetic and DIO models subsequently induced with ischemia. These studies included models of DIO via administration of a high fat diet (36% fat; high in saturated fat) for 10 weeks (Deutsch et al, 2009), administration of a 'Western Diet' for 12 weeks (Langdon et al, 2011), administration of a high fat diet (45% fat) for 8 weeks (Li et al, 2013), TallyHo mice (a model of type II diabetes) (Didion et al, 2007), the ob/ob mouse (Mayanagi et al, 2008;Kumari et al, 2010), the diabetic db/db mouse (Vannucci et al, 2001), and the obese Zucker rat (Osmond et al, 2009;. In the 2009 study by Deutsch et al, the authors found that the middle cerebral arteries (MCAs) from obese rats had smaller lumens and thicker walls.…”
Section: Animal Studies: Vascular Changes Due To a High Fat Diet And mentioning
confidence: 99%